2021
DOI: 10.1111/geb.13356
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation manipulation and terrestrial carbon cycling: The roles of treatment magnitude, experimental duration and local climate

Abstract: Aim Precipitation manipulation experiments have shown diverse terrestrial carbon (C) cycling responses when the ecosystem is subjected to different magnitudes of altered precipitation, various experimental durations or heterogeneity in local climate. However, how these factors combine to affect C cycle responses to changes in precipitation remains unclear. Location Global. Time period 1990–2019. Major taxa studied Terrestrial ecosystems. Methods Using observations from 230 published studies in which precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 70 publications
1
37
0
Order By: Relevance
“…The mechanism explaining the asymmetric responses to the rainfall anomalies resulted from the non‐linear responses of GPP to rainfall. Linear relationships between GPP and rainfall were reported by some in‐situ observations (Felton et al., 2019; Post & Knapp, 2020; Wang et al., 2021). Based on 20 years of remote sensing observations across the NECT region, we showed that GPP presented a saturating response to rainfall anomalies in semi‐arid regions, where negative effects of dry anomalies on GPP are larger than the positive effects of wet anomalies, that is, negative asymmetry.…”
Section: Discussionmentioning
confidence: 63%
“…The mechanism explaining the asymmetric responses to the rainfall anomalies resulted from the non‐linear responses of GPP to rainfall. Linear relationships between GPP and rainfall were reported by some in‐situ observations (Felton et al., 2019; Post & Knapp, 2020; Wang et al., 2021). Based on 20 years of remote sensing observations across the NECT region, we showed that GPP presented a saturating response to rainfall anomalies in semi‐arid regions, where negative effects of dry anomalies on GPP are larger than the positive effects of wet anomalies, that is, negative asymmetry.…”
Section: Discussionmentioning
confidence: 63%
“…If the 95% CI of log e RR did not cover zero, the difference for a variable between labile and more stable SOM was considered significant at α = 0.05. The Shapiro–Wilk test was used to test the normality of the variance of all data, and the fitted coefficients were bootstrapped by 1000 iterations when the normality assumption was violated, using the boot package (Wang et al ., 2021). A linear mixed‐effects model with ‘study’ as a random factor was applied to evaluate the relationships of the log e RR of PE with soil physicochemical properties.…”
Section: Methodsmentioning
confidence: 99%
“…Another overlooked attribute of drought is the effect of duration, and those that have assessed drought duration report conflicting patterns (Estiarte et al, 2016;Gao et al, 2019;Komatsu et al, 2019). Evidence exists that, over time, drought effects can either increase (Felton et al, 2021;Orth et al, 2020), decrease (Wang et al, 2021) or remain unchanged through time (Carroll et al, 2021;Jentsch et al, 2011). The occurrence of a multi-year drought is expected to increase dramatically over this century across North America (Zhao et al, 2020); thus, it is important to ascertain the ecological consequences of prolonged droughts.…”
Section: Introductionmentioning
confidence: 99%